The content and context of physicians' communication with males about human papillomavirus vaccination. Issue 6 (2nd June 2016) - Malo, Teri L.; Ali, Karla N.; Sutton, Steven K.; Perkins, Rebecca B.; Giuliano, Anna R.; Vadaparampil, Susan T.
ABSTRACT: A physician's recommendation for human papillomavirus (HPV) vaccine is a key predictor of vaccine uptake; however, little is known about how physicians communicate about HPV vaccine with male patients. We sought to describe physicians' HPV vaccine communication practices with males who are of vaccine-eligible age (9-26 years). We surveyed representative samples of pediatric and family medicine physicians in Florida, and assessed whether physicians present HPV vaccine as optional or routine, and as a vaccine that prevents cancer. We also assessed the type of visit during which physicians discuss HPV vaccine with adolescent males and whether other healthcare providers in the practice discuss HPV vaccine or make the initial recommendation. We received 367 completed surveys (50.7% response rate). Few physicians (29.9%) reported they typically present HPV vaccine as routine to males ages 11-12 years, who constitute the target group for routine vaccination. When discussing HPV vaccination, many physicians reported somewhat or strongly emphasizing cancer prevention (80.0%). Physicians most often discussed HPV vaccine when they saw patients for well-child visits (93.0%) and least often at acute care visits (15.3%). Over half reported that at least one other healthcare professional in their practice discusses (56.1%) or makes the initial recommendation for (54.9%) HPV vaccination. Many physicians in our sample are presenting HPV vaccine as optional rather than routine and are missing opportunities to communicate with males about the vaccine. Our findings identify areas for future interventions to improve physicians' HPV vaccine communication and, ultimately, increase the use of this cancer-preventing vaccine.